Using and Intensifying Video Modeling for Students With Emotional and Behavioral Disorders. (April 2021) - Zarate, Kary; Maggin, Daniel M.
Video modeling (VM) is a powerful and effective tool to support skill acquisition and generalization for students with and without emotional and behavioral disorders (EBD). Video models can include adults, peers, and the very students at which skill development is directed. This article provides a definition of VM and descriptions of its varying formats, an overview of VM's positive evidence base, reasons why VM is effective, and step-by-step guidance for VM implementation and intensification that meets the needs of students with EBD.